Influência da microestrutura dos ferros fundidos brancos alto cromo e molibdênio no desgaste por deslizamento em alta temperatura - Pinho, Karin Faria (2010)
High-chromium white cast irons are commonly usedin applications requiring excellent abrasion resistance, as in the mining and mineral ore processing industries. Their excellent abrasion resistance is mainly due to their solidification microstructures, constituted typically of hard primary and/or eutectic carbides in a softer iron matrix (i.e. austenitic, martensitic, ferritic, pearlitic or bainitic). The aim of this work is to investigate the influence of the microstructure of these alloys on the wear mechanisms and the level of the friction coefficient during sliding at high temperature. In this study, fifteen experimental high-chromium white cast irons containing different chromium (16 wt.% -32 wt.%) and molybdenum (0 wt.% -9 wt.%) contents with a ratio Cr/C of 10 are examined. The matrix microstructure and the type of carbides depend on the relative contents of Cr and Mo. The wear experiments are carried out on a pin-on-disc tribometer at 700 ºC. The microstructure of the matrix, combined with the volume fraction and average area of carbides, have the most important role in controlling friction. It is observed that the wear losses are less significant compared to those obtained at room temperature. The mean friction coefficient is also lower than those observed at room temperature sliding wear